THE INFLUENCE OF THE PHYSICAL ACTIVITY LEVEL OF FLEXIBILITY IN MUSCLE CHAIN ??BACK IN TEENAGERS FROM 14 TO 18 YEARS. (Fiep Bulletin - online, 2014)
The objective of the study was to verify the influence of the level of physical activity in adolescents' flexibility. The sample included 118 adolescents (14-18 years) from a high school in the city of Imperatriz, Maranhão. Students underwent an anthropometric assessment of weight and height, to characterize the sample, a questionnaire to identify the physical activity level (PAL), and the Sit and Reach test (SRT), to define the flexibility of muscles posterior chain. The level of physical activity was measured using the International Physical Activity Questionnaire (IPAQ) and the flexibility of the muscles of the posterior chain was measured using the sit -and-reach test (SRT) without the Bank Wells. Regarding the PAL, 32 (27.12 %) subjects were classified as sedentary, while 86 as assets (72.88 %). For medium flexibility, as groups, teens reached in the group Active 34.70 cm (95% CI 32.62 to 36.78) and 30.00 cm Sedentary group (95% CI 25.74 to 34, 26), the analysis of the difference between group means (student t) indicated statistically significant difference (p = 0.030). In summary, in this population, active teens have higher average flexibility when compared to sedentary.
Keywords: Physical Activity; Flexibility; Teens